ID 338 – Retinal Nerve Fibre Layer loss is associated with disease progression in Multiple Sclerosis. Issue 3 (March 2016) - Pisa, M.; Di Maggio, G.; Guerrieri, S.; Santangelo, R.; Medaglini, S.; Rodegher, M.; Colombo, B.; Moiola, L.; Del Carro, U.; Martinelli, V.; Comi, G.; Leocani, L.
Abstract : Objective: The visual pathway is receiving increasing attention as a marker to monitor and predict disability progression in Multiple Sclerosis (MS). We investigate the usefulness of visual evoked potentials (VEPs) and optical coherence tomography (OCT) in monitoring MS disability. Methods: We performed VEPs, OCT with measurement of retinal nerve fiber layer (RNFL) and clinico-neuroradiological assessment at baseline and after 2 years follow-up in 75 subjects with MS of whom 59 were analysed, excluding patients with optic neuritis (ON) within 6 months from baseline assessment. Results: Reduction of binocular mean RNFL thickness was correlated (Spearmann rho −0, 587; p  < 0.0001) with increased rate of the expanded disability status scale (EDSS) and it was greater in subjects with neuroradiological or clinical disease activity ( p  < 0.0001, test- T ). The RNFL reduction rate was similar in eyes with or without ON. Although baseline RNFL was correlated with EDSS change at follow-up, this correlation lost significance after correcting for baseline EDSS. Conclusions: Progressive reduction of RNFL can be due to disease activity along the visual pathways or to global neurodegenerative processes. OCT may be more useful for monitoring neurodegeneration rather than as a prognostic indicator. Key message: RNFL loss is associated with disease activity and disability in MS.